Pengaruh Ekstrak Nanas (Ananas Comosus (L) Merr) SEBAGAI Antihelmintik Terhadap Waktu Kematian Cacing Ascaris suum, Goeze In vitro - Dewi, Cindikya Saftiari; SitiUtari, Cr.; Wasita, Brian (Nexus Biomedika, 2013)
Background:Pineapple (Ananas comosus (L) Merr) was reported to have a bromelain enzyme that belonged to a group of proteolytic enzymes. This enzyme has been known as anti-edematous, anti-inflammatory, anti-thrombotic and fibrinolytic activities. The proteolytic effect of bromelain enzyme can change protein to be simple amino acid. This research was performed to understand the effect of pineapple (Ananas comosus (L) Merr) extract as anthelmintic on death time of Ascaris suum, Goeze In Vitro. Methods:This research was performed using experimental laboratory method with the post test only controlled group design. Eighty four adult Ascaris suum, Goeze were used. The worms divided into seven groups consisted of six treatment groups (pineapple (Ananas comosus (L) Merr) extract with the dose of 0 % g/ml, 3 % g/ml, 6 % g/ml, 12 % g/ml, 24 % g/ml and 48 % g/ml) and positive control group (Pirantel pamoat with the dose of 0.236% g/ml). Each group consisted of four worms. Ascaris suum, Goeze were incubated in incubator at 37ÂºC. Observation was performed every fifteen minute to determine the death time of the worms. Experimental data was analyzed using One Way ANOVA test continued with Post hoc Tukey test (Î± = 0.05). LC50 and LT50 were calculated using probit analysis. Â  Results:One Way ANOVA test showed significance difference (p < 0.05). Pineapple (Ananas comosus (L) Merr) extract had a significant effect on the worm death time and showed dose dependent manner. Probit analysis showed that LC50 and LT50 of pineapple (Ananas comosus (L) Merr) extract were 21.059% g/ml and 396.929 minutes. At the concentration of 4% g/ml pineapple extract had a better effect than positive control. Conclusions:Pineapple (Ananas comosus (L) Merr) extract had an effect on the death time of Ascaris suum, Goeze which was showed by significance difference on the death time between treatment and negative control group, and this effect was comparable with positive control group. Keywords:Pineapple (Ananas comosus (L) Merr) extract, bromelain enzyme, Ascaris suum, Goeze, pirantel pamoat